BUILDING AND CODIFYING A MEASURE OF PERCEIVED SELF-EFFICACY AMONG PLAYERS PREMIER LEAGUE FOOTBALL CLUBS - Asst. Lect Sadiq Ibrahim Abdullau; Prof. Dr Abd-Al Kaizm Jalil Hassan; Prof. Dr Majad Sabar Mohammed (Scholars Digest Publishing, 2024)
The importance of this study stems from the fact that it sheds light on the role of psychological factors in sports performance and knowledge of what is related to the characteristics, personal traits and psychological skills of athletes by investing those characteristics and skills within them and exploiting them to raise the level of performance and the effects they may have that could reflect positively on their assigned tasks to increase From the opportunity to win in the future and achieve goals as a result of the player’s perceived self-efficacy, his feeling of self-awareness, satisfaction with his performance, self-confidence, strength, motivation, continued field practice, and excitement, There is no doubt that these psychological factors positively affect the effectiveness of perceived self-efficacy by determining the amount of effort an individual exerts in a particular activity, the amount of his perseverance in the face of obstacles, and the amount of his resilience in the face of difficult situations. The greater the sense of competence, the greater the effort, perseverance, and resilience. Hence the importance of research into constructing, codifying, and applying a measure of perceived self-efficacy to Premier League football clubs. Therefore, this study required the use of a descriptive method using a survey method. For the purpose of constructing, codifying and applying the scale to a sample of Premier League football players for the season (2022/2023), which numbered (430) players from the research community (650) players, The scale was applied in its final form to a sample of (150) players, after statistical transactions were conducted to extract the psychometric characteristics (honesty, reliability, objectivity), and determine their standard levels. The SPSS statistical package was used. This is to obtain, analyze and discuss the results of the study. In light of discussing these results, the researchers reached the most important conclusions: 1- Most of the players of Premier League football clubs were at the average level on the scale of the current study
Keywords: Perceived self-efficacy: Football: Psychological factors.